Two new species of Dracoderes (Kinorhyncha: Dracoderidae) from the Ryukyu Islands, Japan, with a molecular phylogeny of the genus - Yamasaki, Hiroshi (Zootaxa, 2015)
Two new species, Dracoderes snufkini sp. nov. and Dracoderes toyoshioae sp. nov., are described from Okinawa, southern Japan. Diagnostic characters of D. snufkini include: lateroventral tubules on segments 2 and 5; a thick, plump middorsal spine on segments 2 and 9; thick plump paradorsal spines on segments 3–8, alternately laterally displaced; and a ventral primary pectinate fringe on segment 1, with long, wide conspicuous tips. Diagnostic characters of Dracoderes toyoshioae include: a middorsal subcuticular structure on segment 1; paradorsal subcuticular structures on segments 2–9, alternately laterally displaced; paradorsal acicular spines arising from subcuticular structures, at least on segment 5; ventrolateral acicular spines on segment 1; lateral accessory tubules on segment 2; lateral accessory subcuticular structures on segments 2–7; lateroventral tubules on segment 5; and lateroventral subcuticular structures on segments 2–10. Molecular phylogenetic analyses based on 18S rRNA, 28S rRNA and mitochondrial COI sequences indicate that D. abei and D. nidhug are more closely related to one another than either is to D. snufkini or D. toyoshioae.